Volumetric Properties and Resilient Modulus of Stone Mastic Asphalt incorporating Cellulose Fiber - N. A. N., Azman; K. A., Masri; Putra Jaya, Ramadhansyah; Mohd Shamsul Azmi, Samsudin; A., Ismail; A. K., Arshad; E., Shaffie; A. H., Norhidayah; M. R., Hainin (2019)
Stone mastic asphalt (SMA) is well known as a high coarse aggregate content that interlocks to form a stone skeleton that resist permanent deformation. However, it facing a lot of problems such as rutting and stripping because of the high temperature and repeated axial load. It also suffers with creep issue. The cellulose fiber is a type of synthetic fiber that can enhance the properties of asphalt mixture. Thus, the aim of this study is to utilize the cellulose fiber that has high tensile strength to overcome the problem of SMA. Among the tests involve are Resilient Modulus, Marshall Stability and Cantabro Loss. From the results, it shows that the addition of cellulose fiber improved the recovery ability of asphalt binder. From each test, the addition of 0.2% cellulose fiber contributes to lowest value of abrasion, while 0.3% producing highest value of resilient modulus. Thus, the addition of cellulose fiber is capable in enhancing the properties of SMA.